Fast Biofilm Formation and Its Role on Power Generation in Palm Oil Mill Effluent Fed Microbial Fuel Cell - Khan, Maksudur R.; E., Baranitharan; D. M. R., Prasad; Cheng, C. K. (EDP Sciences, 2016)
In the present study, fast formation and characterization of biofilm and its role on power generation in the microbial fuel cell (MFC) were investigated and the biofilm formation was also correlated with electrochemical behavior of the MFC. MFC was operated with palm oil mill effluent as substrate and carbon cloth as electrode. A biofilm comprising electrochemically active bacteria on the anode surface showed crucial effect to enhance the performance of the MFC. Infrared spectroscopy and thermogravimetric analysis confirmed the presence of biofilm and scanning electron microscopy examined a biofilm and microbial clumps on electrode surface. The current density was directly dependent on the biofilm growth and increased significantly during the initial growth. Electrochemical impedance spectroscopy was done to monitor the progress of the anode colonization by the microorganisms in the MFC. The findings of this study demonstrated that biofilm formation facilitated electron transport as well as decreased the charge transfer resistance of the anode and thus increased the power generation in the cell.